2013
DOI: 10.1007/s10899-013-9375-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Return Rate Discrimination in Slot Machine Play

Abstract: The purpose of this study was to investigate the extent to which accurate estimates of payback percentages and volatility combined with prior learning, enabled players to successfully discriminate between multi-line/multi-credit slot machines that provided differing rates of reinforcement. The aim was to determine if the capacity to discriminate structural characteristics of gaming machines influenced player choices in selecting 'favourite' slot machines. Slot machine gambling history, gambling beliefs and kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Ultimately, research indicates that even an extra few seconds of respite between betting behaviours can be a sufficient opportunity to evaluate behaviour and reduce risk-taking and overall gambling expenditure (Corr and Thompson 2014). It is argued that the nature of continuous gambling activities, with minimal natural or enforced breaks in play, creates intense emotional and dissociative states, leading to impaired gambling decision-making and maladaptive responding (Coates and Blaszczynski 2013;Loba et al 2001). Fundamentally, a break in play is required to facilitate suppression of arousal and negative valence and to respond adaptively to negative outcomes (Newman and Lorenz 2003;Verbruggen et al 2012).…”
Section: Instant Depositingmentioning
confidence: 99%
“…Ultimately, research indicates that even an extra few seconds of respite between betting behaviours can be a sufficient opportunity to evaluate behaviour and reduce risk-taking and overall gambling expenditure (Corr and Thompson 2014). It is argued that the nature of continuous gambling activities, with minimal natural or enforced breaks in play, creates intense emotional and dissociative states, leading to impaired gambling decision-making and maladaptive responding (Coates and Blaszczynski 2013;Loba et al 2001). Fundamentally, a break in play is required to facilitate suppression of arousal and negative valence and to respond adaptively to negative outcomes (Newman and Lorenz 2003;Verbruggen et al 2012).…”
Section: Instant Depositingmentioning
confidence: 99%
“…However, structural characteristics of the gambling activity are also crucial determinants of arousal and reinforcement in the development of disordered gambling patterns (Blaszczynski 2013). Research has demonstrated that structural features, such as speed of game (Delfabbro et al 2005), schedule of reinforcement volatility (Coates and Blaszczynski 2013;Dixon et al 2006), maximum bet (Livingstone et al 2008), and near-misses Clark et al 2012), affect the gambler's willingness to continue gambling despite incurring significant losses (Blaszczynski 2013). It is possible that such structural characteristics can influence executive control in the individual in the short-term, including response inhibition and reflection impulsivity, and therefore potentially explain withinsession loss of cognitive control.…”
Section: Size Of Stake and Within-session Loss Of Cognitive Controlmentioning
confidence: 99%
“…Even at moderate levels of engagement EGMs can lead to gambling-related harm, such as excessive monetary and time expenditure (Afifi et al 2014;LaPlante et al 2011). Coates and Blaszczynski (2013) argued that rapid, continuous forms of gambling have elevated risk for harm because of the combination of a variable schedule of reinforcement and an absence of natural breaks-in-play. This combination of structural characteristics may lead to maladaptive responding to reinforcement i.e.…”
Section: Gambling-related Harm and Rapid Continuous Gambling Formatsmentioning
confidence: 99%